2015
DOI: 10.1123/jpah.2013-0126
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Built Environment, Physical Activity, Adiposity, and Health in Adults Aged 46–80 in Shanghai, China

Abstract: The findings can help planners build more pedestrian-friendly communities. They are also useful for creating interventions that are sensitive to possible environmental barriers to physical activity in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 0 publications
2
54
1
1
Order By: Relevance
“…The increase in open space and greenspace in a residential neighborhood can also provide a variety of social and ecological benefits to its residents [38][39][40][41]. In addition, the living environment of residential neighborhoods can benefit from building high-rise apartments in some aspects [42].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in open space and greenspace in a residential neighborhood can also provide a variety of social and ecological benefits to its residents [38][39][40][41]. In addition, the living environment of residential neighborhoods can benefit from building high-rise apartments in some aspects [42].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that PNEO measures such as land use mix entropy [19][20][21], population density [19,21,22], traffic intersection density [13,[23][24][25][26] and proximity to recreation areas [26][27][28] influence the PA levels of older adults. While these types of PNEO measures are reliable in representing the objective physical characteristics of the neighbourhood environment that can strongly influence the PA level in older adults, in some cases, local considerations are also needed.…”
Section: Formulation Of Conceptual Modelmentioning
confidence: 97%
“…The PNES measures were based on the Neighbourhood Environment Walkability Scale-Abbreviated (NEWS-A), which includes the perceived measures of the neighbourhood environment. This scale was considered suitable as many past studies in diverse settings have established a connection between perceived PNE and PA in older adults [26][27][28][29][30][31]. Past studies have also found that perceived PNE (PNES) measures such as perceived residential density [13,27,32], land use diversity [13,27,[32][33][34], accessibility [13,32,34,35], street connectivity [13,32], infrastructure for walking and cycling [34,36], neighbourhood aesthetics [13,32,37], safety from traffic hazards [30,32,34,37] and safety from crime [30,34,37,38] were significantly associated with PA.…”
Section: Formulation Of Conceptual Modelmentioning
confidence: 99%
“…Scores were reverse coded such that higher scores indicated a healthier community. This item has been widely used to assess people's general perception toward health 7,27,29,36 and has been found to predict mortality rates. 47 The current study evaluated community health by calculating the average perceived health score for each county.…”
Section: Dependent and Independent Variablesmentioning
confidence: 99%
“…[21][22][23] Among individual-level factors, socioeconomic status (e.g., income, education), [25][26][27][28] demographics (e.g., age, gender), [27][28][29][30][31] health-related behaviors (e.g., smoking behaviors, alcohol consumption), 12,26,[29][30][31][32] and attitudinal orientation toward health and well-being 21,22,25,30 have been examined as correlates of health. For environmental factors, the home and neighborhood environment (e.g., place of residence, housing quality, food environment), 26,31,[33][34][35][36] the work environment (e.g., programs that support employees' health, access to the workplace), 37,38 the sociocultural environment (e.g., family support, social capital, club and membership association), 28,39 and the natural environment (e.g., weather, air quality) 27,40 have been found to be correlates of health-related outcomes. Most previous social-ecological models have focused on the roles of individual and environmental factors in health-related behaviors, such as physical activity promotion, 23,24,28 but a few studies have used a social-ecological model to explain how individual and environmental factors contribute to community health.…”
mentioning
confidence: 99%